Production of fatty acids in Ralstonia eutropha H16 by engineering β-oxidation and carbon storage - Chen, Janice S.; Colón, Brendan; Dusel, Brendon; Ziesack, Marika; Way, Jeffrey C.; Torella, Joseph P. (PeerJ, 2015)
Ralstonia eutropha H16 is a facultatively autotrophic hydrogen-oxidizing bacterium capable of producing polyhydroxybutyrate (PHB)-based bioplastics. As PHB’s physical properties may be improved by incorporation of medium-chain-length fatty acids (MCFAs), and MCFAs are valuable on their own as fuel and chemical intermediates, we engineered R. eutropha for MCFA production. Expression of UcFatB2, a medium-chain-length-specific acyl-ACP thioesterase, resulted in production of 14 mg/L laurate in wild-type R. eutropha. Total fatty acid production (22 mg/L) could be increased up to 2.5-fold by knocking out PHB synthesis, a major sink for acetyl-CoA, or by knocking out the acyl-CoA ligase fadD3, an entry point for fatty acids into β-oxidation. As ΔfadD3 mutants still consumed laurate, and because the R. eutropha genome is predicted to encode over 50 acyl-CoA ligases, we employed RNA-Seq to identify acyl-CoA ligases upregulated during growth on laurate. Knockouts of the three most highly upregulated acyl-CoA ligases increased fatty acid yield significantly, with one strain (ΔA2794) producing up to 62 mg/L free fatty acid. This study demonstrates that homologous β-oxidation systems can be rationally engineered to enhance fatty acid production, a strategy that may be employed to increase yield for a range of fuels, chemicals, and PHB derivatives in R. eutropha.
Keywords: -oxidation; Acyl-CoA ligase; Ralstonia; Biofuel; Metabolic engineering